2022
DOI: 10.32744/pse.2022.6.37
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gender, Teaching Experience, Educational Background, and the School Type on Teachers’ Mathematical, Didactic, and Technological Competences

Abstract: Introduction. Many previous studies are increasingly rising the issue of teacher competences, specifically on content, didactics and technology. Those competences are considered as important aspects for successful teaching process in the classroom. Therefore, this study shed lights the effects of gender, teaching experience, educational background, and school types on teachers’ mathematical, didactic, and technological competences. Material and methods. The research method is an online survey of 145 elementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The gender issue is not only in CT but also in many aspects of mathematics education studies (Putra, Hermita, Afrillia, et al, 2022;Putra, Hermita, Yuliani et al, 2022;Reilly et al, 2019;Tambak et al, 2022). According to Reilly et al (2019), a large-scale study (TIMSS results from 2011) on the investigation of gender differences in mathematics and sciences found that, while there were no general worldwide gender disparities, female students outperformed male students' mathematics and science proficiency among non-OECD countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gender issue is not only in CT but also in many aspects of mathematics education studies (Putra, Hermita, Afrillia, et al, 2022;Putra, Hermita, Yuliani et al, 2022;Reilly et al, 2019;Tambak et al, 2022). According to Reilly et al (2019), a large-scale study (TIMSS results from 2011) on the investigation of gender differences in mathematics and sciences found that, while there were no general worldwide gender disparities, female students outperformed male students' mathematics and science proficiency among non-OECD countries.…”
Section: Introductionmentioning
confidence: 99%
“…From several studies (Putra, Hermita, Afrillia, et al, 2022;Putra, Hermita, Yuliani, et al, 2022;Reilly et al, 2019;Tambak et al, 2022), it is still apparent that there is a debate between male and female competencies in CT and mathematics. Therefore, the present study is also interested in analyzing whether there were differences in students' CT skills regarding gender differences.…”
Section: Introductionmentioning
confidence: 99%